Rebuilding the ancestral village : Singaporeans in China - Kuah-Pearce, Khun Eng, 1958- (Hong Kong University Press, 2011)
This work illustrates the relationship between one group of Singaporean Chinese and their ancestral village in Fujian China. It explores the reasons why the Singaporean Chinese continue to maintain ties with their ancestral village and how they reproduce Chinese culture through ancestor worship and religion.